Troubleshooting Java : read, debug, and optimize JVM applications - Spilcă, Laurenţiu (Manning Publications, 2023)
Effectively reading and understanding existing code is a developer's superpower. In this book, you'll master techniques for code profiling, advanced debugging, and log evaluation to find and fix bugs and performance problems. In Troubleshooting Java: Read, debug, and optimize JVM applications you will learn how to: Determine what code does the first time you see it Expose code logic problems Evaluate heap dumps to find memory leaks Monitor CPU consumption to optimize execution Use thread dumps to find and solve deadlocks Easily follow a service-oriented or microservices system Properly use logging to better understand Java app execution Use Java debuggers efficiently Searching for bugs, detangling messy legacy code, or evaluating your codebase for new features sucks up much of a developer's time. Troubleshooting Java: Read, debug, and optimize JVM applications teaches code investigation techniques that will help you efficiently understand how Java apps work, how to optimize them, and how to fix the bugs that break them. You'll go from the basics of debugging to advanced methods for locating problems in microservices architectures, and save yourself hours--or even days--of time. Each new technique is explained with lively illustrations and engaging real-world examples. About the Technology Fact: Over the course of your career, you'll spend far more time reading code than you will writing it. The code investigation skills in this book will radically improve your efficiency in understanding and improving Java applications. About the Book Troubleshooting Java: Read, debug, and optimize JVM applications presents practical techniques for exploring and repairing unfamiliar code. In it, you'll learn timesaving practices for discovering hidden dependencies, discovering the root causes of crashes, and interpreting unexpected results. Go beyond profiling and debugging and start understanding how Java applications really work. What's Inside Determine what code does the first time you see it Evaluate heap dumps to find memory leaks Monitor CPU consumption to optimize execution Use thread dumps to find and solve deadlocks Uncover glitches in code logic Locate intermittent runtime problems About the Reader For intermediate Java developers. About the Author Laurențiu Spilcă is a skilled Java and Spring developer and an experienced technology instructor. He is the author of Spring Start Here and Spring Security in Action. Quotes We spend more time trying to understand code than writing it. This book shows you how to use that time wisely. - Brent Honadel, Infor Finally a book that illustrates how to troubleshoot and reason about Java apps in production! It just might save the day! - Atul Shriniwas Khot, SquareOne Insights I wish I had this collection of efficient and usable techniques at the beginning of my career. - Andriy Stosyk, EPAM Systems A great book with deep explanations about debugging techniques. - Cătălin Matei, Endava Understand how Java applications work under the hood. - Fernando Bernardino, Wise.